Effect of a specific concurrent water and dry-land training over a season in young swimmers' performance - Morais, J. E; Silva, A. J; Marinho, D. A.; Marques, M. C.; Barbosa, T. M. (International Journal of Performance Analysis in Sport, 2016)
The aims of this study were to assess over a full season: (i) the effect of a combined dry-land strength and conditioning and in-water program on the swimming performance of young swimmers; (ii) the effect of such program on the performance determinants; (iii) the effect of the training periodization designed. A longitudinal research design assessing an agegroup of young swimmers over a season was carried out. Methods: Twentyseven young swimmers (12 boys: 13.55±0.72-y; 15 girls: 13.16±0.93-y; both sexes in Tanner stages 2-3) were evaluated in three moments over 40 weeks. The 100-m freestyle performance, body mass, height, arm span (anthropometrics), stroke frequency, stroke length, swimming velocity, intracyclic swimming velocity (kinematics), stroke index, propelling efficiency (efficiency), squat jump, countermovement jump, and throw velocity (strength and conditioning) were assessed. A cluster analysis was computed to classify the swimmers. For the "talented" swimmers, the performance and all determinants, but the squat and countermovement jumps improved between the first and last evaluation moments. Both inwater and dry-land strength and conditioning features were responsible for the cluster discrimination in each one of the evaluation moments. All three clusters were also characterized by a mix of technical and strength & conditioning features. This highlights swimming performance as a holistic phenomenon (i.e. multiple determinants) where shifting occur in the interplay among the performance determinant according to the training periodization.